A Unifying Theory of Branching Morphogenesis - Hannezo, Edouard; Scheele, Colinda L.G.J.; Moad, Mohammad; Drogo, Nicholas; Heer, Rakesh; Sampogna, Rosemary V.; van Rheenen, Jacco; Simons, Benjamin D. (Cell, 2017)
The morphogenesis of branched organs remains a subject of abiding interest. Although much is known about the underlying signaling pathways, it remains unclear how macroscopic features of branched organs, including their size, network topology, and spatial patterning, are encoded. Here, we show that, in mouse mammary gland, kidney, and human prostate, these features can be explained quantitatively within a single unifying framework of branching and annihilating random walks. Based on quantitative analyses of large-scale organ reconstructions and proliferation kinetics measurements, we propose that morphogenesis follows from the proliferative activity of equipotent tips that stochastically branch and randomly explore their environment but compete neutrally for space, becoming proliferatively inactive when in proximity with neighboring ducts. These results show that complex branched epithelial structures develop as a self-organized process, reliant upon a strikingly simple but generic rule, without recourse to a rigid and deterministic sequence of genetically programmed events. [Display omitted] •Branching morphogenesis follows conserved statistical rules in multiple organs•Ductal tips grow and branch as default state and stop dividing in high-density regions•Model reproduces quantitatively organ properties in a parameter-free manner•Shows that complex organ formation proceeds in a stochastic, self-organized manner Complex branched epithelial structures in mammalian tissues develop as a self-organized process, reliant upon a simple set of local rules.